2010
DOI: 10.1161/circimaging.109.901561
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Left and Right Ventricular Mechanics During the Mueller Maneuver in Healthy Adults

Abstract: Background— Obstructive sleep apnea is highly prevalent in patients with cardiovascular disease and has detrimental effects on systolic and diastolic function of the ventricles. In this research, the changes in strain (S) and strain rate (SR) during the performance of the Mueller maneuver (MM) in an effort to better understand how negative intrathoracic pressures affect ventricular mechanics. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…There are multiple mechanisms by which OSA could lead to heart remodeling, including exacerbation of nighttime and daytime hypertension, increased sympathetic tone, increased left ventricular afterload due to increased arterial stiffness, and exaggerated swings in intrathoracic pressure during obstructive episodes, among others (6769). The impact of OSA on heart remodeling has recently been explored in obese patients.…”
Section: Can Osa Have Independent Effects On the Cardiometabolic Riskmentioning
confidence: 99%
“…There are multiple mechanisms by which OSA could lead to heart remodeling, including exacerbation of nighttime and daytime hypertension, increased sympathetic tone, increased left ventricular afterload due to increased arterial stiffness, and exaggerated swings in intrathoracic pressure during obstructive episodes, among others (6769). The impact of OSA on heart remodeling has recently been explored in obese patients.…”
Section: Can Osa Have Independent Effects On the Cardiometabolic Riskmentioning
confidence: 99%
“…Moreover, the elevated negative intrathoracic pressure 18 due to upper airway collapse and the consequent mechanical stretching of the LA wall, [19][20] the increased transmural cardiac pressure, and ventricular wall tension and afterload 21 may explain LV remodeling and diastolic and systolic cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Using previously published thresholds, LVH was defined as an LV mass index > 48 g/m 2 for men and > 44 g/m 2 for women. 18 The LV ejection fraction was measured as a LV systolic function parameter with the normal value set at > 55%. Left atrial (LA) mass index, surface, and diameter were also calculated.…”
Section: Echocardiographymentioning
confidence: 99%
“…15 Acute distension of the atrium might be an important trigger for the onset of AF in these patients. 16 Furthermore, negative intrathoracic pressure changes were shown to trigger AF episodes by shortening of atrial effective refractory periods, mainly due to enhanced vagal activation.…”
Section: R Esum Ementioning
confidence: 98%
“…11,30,31 A decline in systolic and diastolic left ventricular function was also found during respiratory events in OSA. 15,32 In addition, SDB affects cardiac electrophysiology by modifying conduction velocity and refractoriness. Rossi and coworkers, for instance, demonstrated that OSA is associated with prolongation of the corrected QT interval and corrected Tpeak to Tend interval intervals and TpTe/ QT ratio.…”
Section: R Esum Ementioning
confidence: 99%